PENGARUH DESAIN PRODUK TREN FASHION DAN CITRA MEREK TERHADAP NIAT BELI JERSEY TIMNAS INDONESIA MELALUI FOMO – STUDI KASUS MEREK ERSPO - Putra, Rafi Risya; Pebrianti, Wenny; Azazi, Anwar; Juniwati; Heriyadi (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
This study aims to examine how product design, fashion trends, and brand image influence consumers' purchase intention toward the Indonesia National Football Team jersey, with Fear of Missing Out (FOMO) as a mediating variable. Data were collected through an online questionnaire via Google Forms using a purposive sampling method, involving 200 respondents interested in the national team jersey. The respondents consisted of consumers who had seen advertisements or promotions for the jersey and expressed interest in purchasing it. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 4.0 to evaluate the relationships between research variables. The results show a positive and significant relationship between product design, fashion trends, and brand image on purchase intention, both directly and indirectly through FOMO as a mediating variable.